Acute Kidney Injury with Characteristics of Rapidly Progressive Glomerulonephritis Due to Suspected IgA Nephropathy: A Case Report - Sandra Yuliana Andini Putri; Nadhila Aditiyaputri; Amanukarti Resi Oetomo (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Acute kidney damage (AKI) in glomerular disease is typically characterized by rapidly progressive glomerulonephritis (RPGN). RPGN in IgA nephropathy is uncommon, occurring in less than 10% of patients. RPGN presents diagnostic issues in resource-limited settings. A 34-year-old male patient had acute kidney injury with RPGN characteristics based on clinical symptoms of hypertension, pitting edema, anuria, and hematuria after an upper respiratory tract infection, as well as laboratory findings of proteinuria, persistent microscopic hematuria, and positive erythrocyte casts. Serum creatinine levels rose sharply. Corticosteroids, antihypertensives, and hemodialysis resulted in clinical improvement and fast kidney function recovery. Due to limited resources, no kidney biopsy was conducted. This case provides a diagnostic approach to RPGN in IgA nephropathy in resource-limited settings, along with comprehensive therapy.